1998
DOI: 10.1017/s0022112098001475
|View full text |Cite
|
Sign up to set email alerts
|

The effects of expansion on the turbulence structure of compressible boundary layers

Abstract: A fully developed Mach 3 turbulent boundary layer subjected to four expansion regions (centred and gradual expansions of 7° and 14°) was investigated with laser Doppler velocimetry. Measurements were acquired in the incoming flat-plate boundary layer and to s/δ≃20 downstream of the expansions. While mean velocity profiles exhibit significant progress towards recovery by the most downstream measurements, the turbulence structure remains far from equilibrium. Comparisons of computed (method of charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 22 publications
4
31
0
Order By: Relevance
“…The primary experimental observation is the increase of the boundary layer thickness. In the measurements of Dawson et al [108] and Arnette et al [109] for a Mach 3 turbulent boundary layer through centered or gradual expansions of 7 (Fig. 48).…”
Section: -D Expansion-compression Cornermentioning
confidence: 91%
See 1 more Smart Citation
“…The primary experimental observation is the increase of the boundary layer thickness. In the measurements of Dawson et al [108] and Arnette et al [109] for a Mach 3 turbulent boundary layer through centered or gradual expansions of 7 (Fig. 48).…”
Section: -D Expansion-compression Cornermentioning
confidence: 91%
“…49) shows that the structures undergo an increase in both scale and angular orientation behind the expansion. Arnette et al [109] suspected that the increase in structure angle is a kinematic effect associated with the acceleration of the bottom of the structure through the inclined expansion region before the top of the structure.…”
Section: -D Expansion-compression Cornermentioning
confidence: 99%
“…Therefore the expansion length Le is set to be Le≥10δ0. The experiments of Dawson et al [10] and Arnette et al [9] for 7° and 14° expansion corners at Ma=3 indicated that the boundary layer remains far from recovery even though the downstream length is 20 times the boundary layer thickness. In this study, to simulate the full recovery process, we only consider two small expansion deflection angles at 2° and 4° and set Le=16δ0≈100mm.…”
Section: Domain and Grid Distributionmentioning
confidence: 96%
“…So far the recovery process of supersonic flow over an expansion corner is not fully understood. For a supersonic flow at Ma=3 with 7° and 14° expansions, experiments by Arnette et al [9] and Dawson et al [10] showed that the boundary layer remains far from fully recovered 19.3δ downstream of the expansion corner (δ is the incoming boundary layer thickness). Measurements of Dussauge and Gaviglio [4] even showed that the incoming boundary layer re-laminarized downstream and the subsequent evolution of the outer part of the boundary layer is very slow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation